Theorizing News Literacy Behaviors. Issue 1 (6th May 2020) - Vraga, Emily K; Tully, Melissa; Maksl, Adam; Craft, Stephanie; Ashley, Seth
Abstract: Despite renewed interest in news literacy (NL) as a way to combat mis- and dis-information, existing scholarship is plagued by insufficient theory building and inadequate conceptualization of both "NL" and its application. We address this concern by offering a concise definition of NL and suggest five key knowledge and skill domains that comprise this literacy. We distinguish NL from its application to behaviors that communication scholars have been interested in, including news exposure, verification, and identifying misinformation. We propose an adapted Theory of Planned Behavior (TPB) to include NL in addition to the existing components (attitudes towards the behavior, social norms, perceived behavioral control) when modeling NL Behaviors. We discuss how this model can unite scholars across subfields and propose a research agenda for moving scholarship forward.